Dr. Anwar Ahmad as a Columnist - ur Rehman Shah, Mujeeb; Rafiq, Robina (sourcecoder, 2022)
Dr. Anwaar Ahmad is a columnist, critic and a famous short storywriter. He wrote the columns in "Daily Duniya" with the title "wada Khilafi". He also writes in the online newspaper "Gird o paish". His columns are full of beautiful sentences, and thought provoking topics and ideas. His criticism on the present situations paves the paths for radical thinking and mindfulness. The specificity of these columns is nutrition and training of the intellect. These columns are assets for the future. This research artical reflects the contribution of Anwar Ahmad in journalism. In this article, some bright and specific aspects of his columns writing have been stated.